Implementation of environment-based learning model at the elementary education level: a systematic literature review - Suhartono, Suhartono; Salimi, Moh; Hidayah, Ratna; Fauziah, Muna; Jupriyanto, Jupriyanto (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
Literature reviews on the implementation of environmental-based learning models at the elementary education level are still very limited. This study uses a systematic literature review method on the implementation of environmental-based learning models at the elementary education level. The research data was taken from the Scopus and Google Scholar databases, which are the main sources of information. The data was processed using the PRISMA method. In data collection, there are several keywords used such as